Hospitalizations and inpatient mortality for hyperosmolar hyperglycemic state over a decade. (March 2022) - Shaka, Hafeez; El-amir, Zain; Wani, Farah; Albosta, Michael; Dahiya, Dushyant Singh; Alabi, Omolabake; Muojieje, Chukwudi Charles; Kichloo, Asim
Abstract: Objectives: This study aimed to describe rates and trends in hospitalizations, inpatient mortality, total hospital charges, and mean lengths of stay among adult patients hospitalized for hyperosmolar hyperglycemic state (HHS). Methods: The study included NIS databases 2008, 2010, 2012, 2014, 2016, and 2018. These databases were searched for hospitalizations with a principal discharge diagnosis of HHS in patients with T2DM using ICD codes (25020, 25022, and E110). Patients less than 18 years, elective hospitalizations, HHS in patients with T1DM or secondary diabetes mellitus were excluded. We used multivariable regression analysis to obtain trends in mortality, length of stay (LOS), and total hospital charges (THC). Results: Between 2008 and 2018, there was a trend towards increasing hospitalizations for T2DM with HHS (p trend < 0.001). The mean age over the period ranged from 56.9 to 59.1 years old. Men made up the majority of hospitalizations. Over the decade, there was a steady rise in the proportion of Whites and Hispanics with HHS, and Medicare was the most prevalent insurer overall. Inpatient mortality for HHS decreased from 1.44% in 2008 to 0.77% in 2018 (p trend 0.007). There was also a statistically significant decrease in both LOS and THC over the studied period. Conclusions: Trends in HHS showed increased hospitalizations, LOS, and THC over the decade in the study period, but inpatient mortality declined.